Integrasi Sistem Informasi Bidikmisi di Politeknik Negeri Padang - Rasyidah; Humaira (SOTVI - Society of Visual Informatics, 2020)
Bidikmisi scholarships are scholarships given by the government to prospective students who have economic limitations but have good academic potential. Every year the bidikmisi enthusiasts in Padang State Polytechnic increase, the manager needs to prepare activities to select the prospective bidikmisi recipients as well as possible. In the selection process for Bidikmisi scholarship recipients, it is necessary to conduct a visitation activity or visit from the Padang State Polytechnic to the residence of prospective Bidikmisi students to ensure that the data provided is correct. Therefore, a bidikmisi information system was made in Padang State Polytechnic with a web application as a server side that can validate data and a mobile application (android) as a client side that can change data at the destination without the internet to select prospective bidikmisi recipients. Bidikmisi Information System web application in Padang State Polytechnic was built using the PHP programming language with the Framework Framework while in a mobile application (Android) it was built using the Java programming language. In designing the integration of Bidikmisi information systems in Padang State Polytechnic the tools used are UML (Unified Modeling Language) which consists of use case diagrams, class diagrams, activity diagrams and sequence diagrams